Pengembangan Industri Maritim di Nusa Tenggara Barat (NTB): Peluang dan Tantangan - M Firmansyah; M Masrun; B Busaini (Ecoplan, 2021)
One of the West Nusa Tenggara Governor's (2018-2023 era) mission is to encourage industrialization. This research tries to provide answers related to opportunities in the fisheries sector for industrialization and its challenges. The study was conducted with a qualitative approach. Qualitative (primary) data was obtained by conducting interviews with several experts in marine and fisheries and through FGD with related agencies. In contrast, secondary data was obtained from the fishing and marine services of (DKP) NTB Province. The results showed that NTB's fisheries were still relatively large in production and the area of fish land (capture and cultivation). And also, Non-fish production is suitable to be used as the main source of industrialization. However, several obstacles that need to be addressed, such as low human resources, infrastructure, supervision, and law enforcement of illegal practices in fisheries, low fiscal support and coordination among stakeholders, have not been resolved. Data validity is needed to be related to fisheries aspects, cross-stockholder forums such as Maritim product investment forums consisting of government, academia, and the business world, and directing industrial development towards the industrial Maritim cluster (ICM).